2023
DOI: 10.3324/haematol.2022.282605
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenetic landscape and clinical impact of <i>BCL11B</i> alterations in adult and pediatric T-cell acute lymphoblastic leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…or MDS, the reason is thought that lower BCL11B related lower T cell activity. 18,36 In contrast, BCL11B is also considered as oncogene in T-ALL, 22,37 overexpression of BCL11B is frequently identified in T-ALL, inhibition of BCL11B effectively induces growth retardation and apoptosis of T-ALL cells. [22][23][24]38,39 These findings were consistent with present study that TCL patients harboring BCL11B mutation might predict favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…or MDS, the reason is thought that lower BCL11B related lower T cell activity. 18,36 In contrast, BCL11B is also considered as oncogene in T-ALL, 22,37 overexpression of BCL11B is frequently identified in T-ALL, inhibition of BCL11B effectively induces growth retardation and apoptosis of T-ALL cells. [22][23][24]38,39 These findings were consistent with present study that TCL patients harboring BCL11B mutation might predict favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with a previous report. 10 However, patients with T-ALL harboring a missense mutation of BCL11B which was the most common type of mutation had a lower percentage of CR (42.9% vs 88.2%, P < .001) and negative MRD (38.5% vs 58.3%, P = .173) (Figure S2). Therefore, CR or MRD was not associated with the most common type of mutation, but rather positively correlated with the overall BCL11B mutation.…”
mentioning
confidence: 99%
“…Therefore, the prognostic value in this study was similar to the published articles on different types of diseases. 9 Moreover, a previous report found that BCL11B mutations predict better OS and event-free survival for patients with adult and pediatric T-ALL and may be a potential biomarker for risk stratification in T-ALL 10 ; the relationship between BCL11B mutations and T cells in T-ALL, and the prognostic importance, still remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation